Atrial fibrillation in coronary artery disease patients: gut microbiota composition and echocardiography indexes - Melnychuk, Iryna; Sharayeva, Maryna (ScienceRise: Medical Science, 2023)
The aim: to find connections between gut microbiota composition and transthoracic echocardiography (TTE) indexes in patients with coronary artery disease (CAD) and atrial fibrillation (AF). Materials and methods: 300 patients were divided into 3 groups: first (CAD) – 149 patients with CAD but without arrhythmias; second (CAD+AF) – 124 patients with CAD and AF paroxysm; and the control group – 27 patients without CAD and arrhythmias. 16-S rRNA sequencing checked gut microbiota composition. TTE was done by ALOKA SSD-5000. Results: The II group patients were characterized by the increase of LAD (10.03 %), LAV (15.40 %) and LAVI (11.48 %) in comparison with the I group, P<0.05. The II group patients were characterized by a rise of Pseudomonadota in comparison with the I group, P<0.05. Also, II group patients were characterized by rise of Actinobacter Spp. and decrease of Blautia Spp., Bacteroides Thetaiotaomicron in comparison with the I group, P<0.05. Firmicutes were correlated with AO (r=0.308), LADI (r=-0.363), RV (r=-0.470), IVS (r=-0.381), LVPW (r=-0.345), LVM (r=-0.476) and EF (r=0,312), P<0.05. Akkermansia Muciniphila was correlated with LAD (r=-0.343), LADI (r=-0.308), LAV (r=-0.494), LAVI (r=-0.488), RAV (r=-0.316), RAVI (r=-0.397), RV (r=-0.383), EF (r=0.332), P<0.05. Bifidobacterium Spp. were correlated with LAV (r=-0.487), LAVI (r=-0.327), RV (r=-0.341), IVS (r=-0.306), RWT (r=-0.389), LVM (r=-0.369), LVMI (r=-0.312), EF (r=0.317), P<0.05. Streptococcus Spp. were correlated with AO (r=0,329), LVOT (r=0,390), RV (r=0,393), IVS (r=0,648), LVPW (r=0,579), RWT (r=0,356), LVM (r=0,336), LVMI (r=0,376), P<0.05. Ruminococcus Spp. were correlated with AO (r=0,412), LVOT (r=0,351), LADI (r=-0.343), IVS (r=-0.316), LVPW (r=-0.367), LVM (r=-0.302), LVMI (r=-0.379), P<0.05. Conclusion: Gut microbiota composition and TTE indexes play a significant role in CAD and AF pathogenesis. Firmicutes, Bifidobacterium spp., and Verrucomicrobiota (Akkermansia muciniphila) were significantly correlated with left atrium size and volume, as well as their ultrasound indexes. Bifidobacterium spp., Bacteroides Spp., Streptococcus Spp. and Ruminococcus Spp. were significantly correlated with left ventricular sizes and its hypertrophy indexes